Monitoring Kualitas Air Tambak dengan Fitur Plug and Play dengan Metode State Machine - Iqbal Yuan Avisena; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Based on good management of pond water quality, it can increase the productivity of the pond if carried out in accordance with appropriate standards. However, most people don't know how to start a good pond cultivation. This test aims to determine how effective the water quality testing is on the pond, with the Plug and Play feature and the State Machine method. In addition, it also aims as a technological development that has been done before. For this reason, the author has designed a pond water quality monitoring system using state machines that are connected to existing supporting sensor nodes through local wireless networks on the node server. The types of sensors used by the authors are pH sensors, temperature sensors, photo diode sensors and nodeMCU as microcontrollers that are used as well as node servers. The readings from these sensors will be sent to the node server via the Broadcat SSID that has been connected by each sensor node. In testing that has been done by the author, the results of sending data by the three sensor nodes used can be sent with an accuracy value of more than 90% of the total data transmission.